Molecular Docking and Antihypertensive Activity of Eupalitin 3-O-β-D-galactopyranoside Isolated from Boerhavia diffusa Linn - Ilyas Uoorakkottil; Rashid Koottangodan; Kamal Y. Thajudheen; Saad Ali Alsheri; Mohammed Muqtader Ahmed (Pharmaceutics)
Background: Angiotensin-converting enzyme (ACE) is a key regulator of blood pressure, and ACE inhibition is an essential part of the treatment of hypertension. We used a molecular docking approach to find the interaction of ACE with an active flavonoid isolated from Boerhavia diffusa Linn, eupalitin 3-O-β-D-galactopyranoside, which leads to potential antihypertensive effects in methyl predenisolone-induced hypertensive rats. Additionally, the pharmacokinetic parameters of this compound are assessed. Methods:eupalitin-3-O-β-D-galactopyranoside was isolated from leaves of Boerhavia diffusa by sedimentation method. The compound was characterized by UPLC-MSMS, NMR, and UV spectroscopy to confirm the identity of the compound. Hypertension was induced in rats with methyl predenisolone (5 mg/kg/day) for 14 days. Systolic and diastolic blood pressure effects of eupalitin 3-O-β-D-galactopyranoside were assessed using a tail-cuff method. The blood plasma data for oral administration were used to determine various pharmacokinetic parameters from the bioavailability and serum concentration. Results: In methyl predenisolone-induced hypertensive rats, both systolic and diastolic blood pressures were significantly lower than that of the vehicle with treatment from eupalitin 3-O-β-D-galactopyranoside (p < 0.01). Conclusions: The pharmacokinetic process showed the moderate bioavailability of the compound; eupalitin 3-O-β-D-galactopyranoside induces powerful antihypertensive activity in methyl predenisolone-induced hypertensive rats, implying potential clinical application as a new therapeutic drug for hypertension.